Tick-borne viral encephalitis in the Tomsk Region for the last decade - I. N. Udintseva; T. N. Poltoratskaya; A. V. Shikhin; A. M. Poponina; N. G. Zhukova; L. V. Lukashova; L. A. Malysheva (Бюллетень сибирской медицины)
In the given work had been lead the analysis of epidemiological data TBE for 1999—2009 on Tomsk area. The information on quantity imparted against tick-borne encephalitis, about results of research of pincers and blood at the persons who have addressed on points prevention of tick-borne encephalitis and about quantity of the diseased tick-borne encephalitis is presented. Analysis of a complex of preventive actions is spent. The reasons of formation of the long maintenance of a virus tick-borne encephalitis in blood are shown.